Hubble Space Telescope Observations of the Interstellar Interloper 3I/ATLAS - David Jewitt; Man-To Hui; Max Mutchler; Yoonyoung Kim; Jessica Agarwal (The Astrophysical Journal Letters)
We present high-angular-resolution observations of the third known interstellar interloper, 3I/ATLAS, from the Hubble Space Telescope. The object is clearly active at 3.8 au preperihelion, showing dust emitted from the hot, Sun-facing side of the nucleus and a weak, radiation-pressure-swept tail away from the Sun. We apply a simple model to estimate the mass loss rate in dust as dM / dt ∼ 12 ${a}_{μ }^{1/2}$ kg s ^−1 , where a _μ is the mean particle size in microns. With 1 ≤ a _μ ≤ 100, we infer dM / dt ∼ 12–120 kg s ^−1 . A fit to the surface brightness distribution of the inner coma limits the effective radius of the nucleus to r _n ≤ 2.8 km, assuming red geometric albedo 0.04. Conversely, the nucleus cannot be smaller than ∼0.22 km in radius if its coma is supplied by sublimation of carbon monoxide and must be larger if a less volatile molecule drives the mass loss.